The efficacy of isoniazid prophylaxis in renal transplant recipients in a high tuberculosis burden country. Issue 5 (16th August 2021) - Dodani, Sunil Kumar; Nasim, Asma; Aziz, Tahir; Naqvi, Anwar
Abstract: Introduction: Renal transplant recipients are at high risk of tuberculosis (TB). We started isoniazid (INH) prophylaxis of 1 year duration in all renal transplant recipients from April 2009. Our aim was to assess the incidence of TB on INH prophylaxis and its tolerability. Methods: This was a retrospective observational study. The files of renal transplant recipients from April 2009 to December 2011 were reviewed till June 2015. We noted the incidence of TB, INH tolerability, and development of resistance. We compared the incidence of TB with the historical controls who never received the prophylaxis. Results: A total of 910 patients were reviewed and followed up for 4.8 years. INH prophylaxis was completed by 825 (91%) patients. A total of 46 patients (5%) developed active TB as compared to 15% in the historical controls. The median time of TB diagnosis from transplantation was 2.8 years. In the first‐year post transplant, out of total TB cases, 52% occurred in the historical controls whereas 13% occurred in study cohort. Around 67% had TB >2 years after transplant. Overall 1.43% had hepatotoxicity. There was a significant reduction in TB among those who completed prophylaxis to those who did not ( p  < 0.001). Of 14 cultures, one isolate was INH resistant (7%). Conclusion: INH prophylaxis was well tolerated. The incidence of TB decreased in the first 2 years. However there was a surge in TB cases 1 year after stopping INH therapy. We should consider prolonging the duration of INH prophylaxis in high TB burden countries in renal transplant recipients.